2002
DOI: 10.1007/s00330-001-1297-7
|View full text |Cite
|
Sign up to set email alerts
|

Effective radiation dose from semicoronal CT of the sacroiliac joints in comparison with axial CT and conventional radiography

Abstract: The aim of this study was to evaluate the radiation dose given by semicoronal CT of the sacroiliac joints (SIJs) in comparison with axial CT and conventional radiography. The total effective radiation doses given by serial contiguous semicoronal and axial CT, using 5-mm slices, 120 kV and 330 mAs, were determined by measurement of organ doses using an anthropomorphic Rando Alderson phantom paced with thermoluminescence dosimeters. The doses given by conventional anteroposterior (AP) and oblique projections of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…In the current study on a retrospective material, no measurements concerning radiation dose were made. In a study by JURIK et al (35) measuring effective dose, the dose to female gonads was reported to be 2.5 times lower for a semi-coronal CT examination (102 mSv) than for a single anteroposterior (AP) radiograph (255 mSv), and more than six times lower than for axial CT (678 mSv). However, the effective semi-coronal CT dose for men (100 mSv) was more than twice that of an AP radiography (39 mSv) when using effective lead shielding of the male gonads at radiography and CT.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study on a retrospective material, no measurements concerning radiation dose were made. In a study by JURIK et al (35) measuring effective dose, the dose to female gonads was reported to be 2.5 times lower for a semi-coronal CT examination (102 mSv) than for a single anteroposterior (AP) radiograph (255 mSv), and more than six times lower than for axial CT (678 mSv). However, the effective semi-coronal CT dose for men (100 mSv) was more than twice that of an AP radiography (39 mSv) when using effective lead shielding of the male gonads at radiography and CT.…”
Section: Discussionmentioning
confidence: 99%
“…CT of the SIJs is associated with radiation exposure. Although optimal machine settings, the use of only a few slices (15,19), or a semicoronal scan plane (27) can reduce the radiation dose, it is more desirable to avoid radiation completely. This can be achieved by replacing CT with MR, though still keeping in mind the situations in which CT is superior to MR, i.e., detection of chronic bone changes in the ligamentous portion of the joint (29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, radiography, CT, and bone scintigraphy all give a radiation dose to the patient. In a study from 2002, it was reported that the effective dose from a semicoronal CT of the sacroiliac joints is 100  μ Sv for men and 102  μ Sv for women, compared to anterior-posterior (AP) projection radiography of the sacroiliac joints resulting in 39  μ Sv for men and 255  μ Sv for women [30]. Dose levels for sacroiliac joint CT from modern multidetector CT scanners with modern dose reducing image reconstruction algorithms are not available.…”
Section: Discussionmentioning
confidence: 99%